Elastoplastic analysis of anchored tunnel under seepage. Issue 3 (May 2019) - Gu, Shuancheng; Li, Xiaodong; Hu, Xiaokai; Wang, Bin; Wang, Yaping
Abstract: In order to study the stress and displacement distribution of surrounding rock of full-length bonded anchor support tunnel under seepage. The surrounding rock is regarded as a uniform and continuous porous medium. The supporting reaction force and seepage force of the surrounding rock are converted into the axisymmetric radial volume force of the circular tunnel and act on the stress field. Considering the reinforcement of the surrounding rock parameters by the bolt, the mechanical model is established. The elastoplastic analysis method is used to derive the analytical solution of the stress and displacement elasticity of the surrounding rock and plastic analytical solution based on Mohr-Coulomb yield criterion, which can be used to obtain the expression of the radius of the plastic zone of the tunnel and the displacement of the wall. Finally, the calculation results of this paper are compared with the numerical simulation analysis. The results show that the influence of the seepage on the plastic zone range and the wall displacement is more serious. The length and pretension of the bolt are inversely related to the plastic zone range and the displacement of the wall. The bolt row spacing is positively correlated with the plastic zone range and the displacement of the wall. Under the same conditions, considering the seepage requires the anchor to provide greater support. In order to avoid the instability of tunnel caused by seepage, the length of the bolt can be reasonably increased, the bolt spacing can be reduced, and the bolt pretension can be increased.